Method and system for acquiring mechanical characteristics of ultra-thin nanofilm materials

By conducting indentation tests with different penetration depths on ultra-thin nano-films and applying the Oliver-Pharr model, the problem of difficulty and low accuracy in testing the mechanical properties of ultra-thin nano-films in the existing technology has been solved, and the control of nano-films has been achieved. and accurate calculation and testing of elastic modulus of base materials.

CN115165527BActive Publication Date: 2025-01-21JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210539374.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-17
Publication Date
2025-01-21
Estimated Expiration
2042-05-17

AI Technical Summary

Technical Problem

The prior art is difficult to effectively test the mechanical properties of ultrathin nanofilms (film thickness <200nm), especially in meeting the 10% critical pressing depth criteria and testing the properties of unknown substrate materials.

Method used

By conducting indentation tests with different penetration depths on the nanofilm, using a sharp indenter and the Oliver-Pharr model, the reduced modulus of the film-base system was extracted, and the elastic modulus of the nanofilm and base material was calculated through formula fitting. .

Benefits of technology

It achieves accurate evaluation of the mechanical properties of ultra-thin nanofilm materials, breaks through the limitations of the 10% critical indentation depth criterion, and can accurately test unknown substrate material properties, reducing the requirements for nanoindentation testing instruments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115165527B_ABST
    Figure CN115165527B_ABST
Patent Text Reader

Abstract

The present invention provides a method and system for acquiring mechanical characteristics of ultra-thin nano-film materials. Firstly, an indentation test at different indentation depths is performed on a nano-film material with a known film thickness to ensure that the maximum indentation depth is greater than the film thickness, a nano-film pressure-through working condition is constructed, and a corresponding film-substrate system reduced modulus is extracted; according to the relationship between the film-substrate system reduced modulus and the maximum indentation depth, the elastic modulus of the nano-film and the substrate material is calculated by using a fitting formula; the present invention breaks through the technical limitation that it is difficult for an ultra-thin nano-film to meet the classic 10% critical indentation depth criterion, and solves the problems of the existing ultra-thin nano-film testing being difficult, having low precision, and having high requirements for nano-indentation testing instruments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanofilm mechanical property testing, and in particular relates to a method and system for acquiring mechanical characteristics of ultra-thin nanofilm materials based on nanofilm pressure penetration conditions. Background Art

[0002] As thin film materials contribute more and more to emerging scientific research and production applications such as optoelectronics, microelectronics and MEMS devices, they promote the miniaturization, intelligence and integration of devices. Among them, the most widely used thin film materials are usually partially constrained films, that is, a layer of functional materials with different properties from the substrate material is prepared on the surface of a metal or non-metal substrate, thereby forming a thin film-substrate system (referred to as "film-substrate system"). Compared with the bulk substrate, the thickness of the thin film material is very thin, often only at the nanoscale or even a few layers of atoms, and external factors such as the preparation process, substrate properties, and interface characteristics have a great influence on the performance of the film-substrate system, making the properties of the thin film material and the bulk substrate material properties significantly different. Therefore, it is very necessary to test the mechanical properties of ultra-thin nano-film materials.

[0003] At present, there are many methods for testing the mechanical properties of nano-thin films. Among them, the intrinsic mechanical properties obtained by free film testing are the most direct and accurate, mainly including uniaxial tension method, tympanic membrane method and thin film microbridge / beam flexure method. However, due to the small thickness of the film, it is more difficult to obtain free films, the preparation process is more complicated, the cost is increased, and the mechanical parameters of nano-thin films are calculated with large errors due to factors such as the clamping method and the sensitivity of the geometric size of the prepared sample.

[0004] Therefore, methods for directly testing and characterizing constrained thin film materials have also emerged. Among them, the most widely used method is the nanoindentation test characterization method, and classic models such as Doerner-Nix, Song-Pharr, and Gao have emerged. However, the test methods for the mechanical properties of the above-mentioned nano-thin film materials usually need to meet the 10% critical indentation depth criterion, that is, the maximum indentation depth cannot exceed 10% of the film thickness. However, this condition is usually difficult to meet directly for indentation tests on ultra-thin nano-films (film thickness <200nm), and the above-mentioned models often require known substrate material properties, which will directly lead to technical limitations such as difficulty in testing the mechanical properties of such ultra-thin films, low precision, and high requirements for nano-indentation testing instruments. Summary of the invention

[0005] The purpose of the present invention is to provide a method for acquiring the mechanical characteristics of ultra-thin nanofilm materials, to break through the existing technical limitations of ultra-thin nanofilms (film thickness <200nm) that are difficult to meet the classic 10% critical indentation depth criterion, and to solve the problems of existing ultra-thin nanofilm testing being difficult, having low precision, and having high requirements for nanoindentation testing instruments.

[0006] The purpose of the present invention is to accurately evaluate the mechanical properties of ultra-thin nanofilm materials based on the nanofilm penetration condition, by using a sharp indenter to carry out a series of indentation tests with different penetration depths on the nanofilm, and specifically includes the following steps:

[0007] Step 1, judging whether the nanofilm in the film-substrate system to be tested meets the nanoindentation test requirements; the thickness t of the nanofilm is known;

[0008] Step 2: Carry out n times of different maximum indentation loads P on the membrane-substrate system to be tested that meets the test requirements i Indentation test, the indenter is pressed into the surface of the nanofilm, and the maximum indentation depth is h i >thickness t, and obtain the indentation load-depth curve;

[0009] Step 3: Extract different maximum indentation loads P according to the indentation load-depth curve through the Oliver-Pharr model. i The reduced modulus E of the membrane-substrate system ri ;

[0010] Step 4: According to the reduced modulus E ri , Maximum penetration depth h i The elastic modulus E of the nanofilm in the film-substrate system to be tested is calculated by fitting the formula (1) and the thickness t. f and the elastic modulus E of the substrate s ;

[0011]

[0012] In formula (1), χ is a correction factor, which is determined by the contribution of the base effect at the critical penetration depth; i = 1, 2, 3, ..., n.

[0013] As a more preferred technical solution of the present invention, the correction factor χ described in formula (1) is calculated as follows:

[0014] When h i →t, then E ri =χE f , the correction factor χ is calculated according to formula (2);

[0015]

[0016] Where: G r is the reduced shear modulus of the membrane-substrate system, G s is the shear modulus of the substrate, G f is the shear modulus of the nanofilm to be tested, G j By the reduced modulus E j and Poisson's ratio j Equivalent calculation, j represents the subscript of different test systems; I1 is the contribution factor of the film to the membrane-substrate system, and a is the contact radius.

[0017] As a more optimal technical solution of the present invention: the compression load-depth curve has no obvious "sudden advance" or "sudden retreat" phenomenon.

[0018] As a more optimal technical solution of the present invention: the Poisson's ratio υ j is 0.1-0.5, preferably Poisson's ratio υ j is 0.3.

[0019] Another object of the present invention is to provide a system for acquiring mechanical characteristics of ultra-thin nano-film materials, the system comprising:

[0020] A loading unit, used for applying n different loads to the membrane-substrate system to be tested;

[0021] A detection unit, used to detect the penetration depth of the indenter and record the relationship between the penetration depth and the penetration load;

[0022] The reduced modulus calculation unit is used to calculate the reduced modulus of the membrane-substrate system under each indentation load through the Oliver-Pharr model according to the relationship between the depth and the indentation load;

[0023] A mechanical characteristic acquisition unit is used to obtain the mechanical characteristic according to the reduced modulus E ri , Maximum penetration depth h i The elastic modulus E of the nanofilm in the film-substrate system is calculated by fitting the thickness t f and the elastic modulus E of the substrate s , the formula is formula (1):

[0024]

[0025] Where: χ is the correction factor, which is determined by the contribution of the base effect at the critical penetration depth; i = 1, 2, 3, ..., n.

[0026] The beneficial effects are as follows:

[0027] The present invention obtains the mechanical properties of ultra-thin nano-film materials based on the pressure penetration conditions of nano-film materials. It can not only break through the technical limitation that ultra-thin films (film thickness <200nm) are difficult to meet the classic 10% critical penetration depth criterion, but also can perform accurate test and characterization on nano-films with unknown substrate material properties, that is, it can simultaneously obtain the elastic modulus of the nano-film and the substrate material, providing a new method for studying the mechanical properties of ultra-thin nano-films.

[0028] In addition, the present invention has low requirements on the loading capacity of the indentation testing instrument, does not require advanced modes such as dynamic mechanical testing, and has a simple testing process.

[0029] Therefore, the method of the present invention for obtaining the intrinsic mechanical properties of thin film materials based on typical nano-film pressure penetration conditions can be promoted and applied as a more universal material testing and characterization method. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings described herein are used to provide further understanding of the present invention and constitute a part of this application. The illustrative examples of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0031] Figure 1 The present invention is a flow chart of the method for obtaining the mechanical characteristics of ultra-thin nano-film materials.

[0032] Figure 2 It is a schematic diagram of the cross section of an equivalent conical indenter penetrating a nanofilm; Figure 2 In the figure, 1 is a sharp indenter; 2 is a loading axis; 3 is a nanofilm; 4 is a reference plane; 5 is a substrate material; 6 is a film-substrate interface; and 7 is an indentation morphology.

[0033] Figure 3 The indentation load-displacement curve of the commercial ITO film Bosch indenter at different indentation depths in Example 1.

[0034] Figure 4 This is a functional relationship curve between the reduced modulus of the film-substrate system and the indentation depth in the commercial ITO thin film indentation test in Example 1. DETAILED DESCRIPTION

[0035] The details of the present invention and its specific implementation methods are further described below in conjunction with the accompanying drawings.

[0036] The acquisition method provided by the present invention first performs an indentation test at different indentation depths on a nanofilm material with a known film thickness to ensure that the maximum indentation depth is greater than the film thickness, constructs a nanofilm pressure penetration condition, and extracts the corresponding film-substrate system reduced modulus; then, based on the relationship between the film-substrate system reduced modulus and the maximum indentation depth, the elastic modulus of the nanofilm and the substrate material is calculated using a fitting formula.

[0037] The present invention provides a method for testing the mechanical properties of thin film materials based on nano-film pressure penetration conditions. Figure 1 The specific steps are as follows:

[0038] Step 1: Select a nanofilm 3 material with excellent smoothness and flatness that meets the requirements of the nanoindentation test as the test object, and firmly bond it to the stage to ensure the smooth progress of the subsequent indentation test.

[0039] Step 2: Use a sharp indenter 1 with geometric self-similar properties, such as a Bosch indenter, to perform n indentations on a nanofilm 3 with a known film thickness t with different maximum indentation loads P. i (i=1,2,3,……,n) indentation test, the corresponding maximum indentation depths are h i (i=1,2,3,……,n), and satisfies h i >t.

[0040] Step 3: To ensure the repeatability and reliability of the test results, each indentation load was tested for repeatability no less than 5 times. At the same time, it was required that there were no significant microcracks, peeling, debonding of the membrane-substrate interface, and other surface and interface damage phenomena during the indentation process. Therefore, the indentation load-depth (Ph) curve without obvious "advance" or "retreat" was selected for data analysis. Then, the reduced modulus E of the membrane-substrate system at different indentation loads was extracted through the classic Oliver-Pharr model. ri .

[0041] Step 4: According to E ri 、h i and t, and use formula (1) and formula (2) to fit and calculate the elastic modulus E of the nanofilm 3 and its base material 5 f and E s , where formula (1) is as follows:

[0042]

[0043] In the formula: when h i >>t, that is, h i →+∞, then E ri =E s ; When h i →t, then E ri =χE f , where χ is the correction factor determined by the contribution of the substrate effect at the critical indentation depth (i.e., film thickness t), and the calculation formula is as follows:

[0044]

[0045] Where: Gr is the reduced shear modulus of the membrane-substrate system, G s is the shear modulus of the substrate, G f is the shear modulus of the nanofilm to be tested, G j By the reduced modulus E j and Poisson's ratio j Equivalent calculation, j represents the subscript of different test systems; I1 is the contribution factor of the film to the membrane-substrate system, and a is the contact radius.

[0046] In some embodiments, the correction factor x described in formula (1) is calculated as follows:

[0047] When h i →t, then E ri =χE f , the correction factor χ is calculated according to formula (2);

[0048]

[0049] Where: G r is the reduced shear modulus of the membrane-substrate system, G s is the shear modulus of the substrate, G f is the shear modulus of the nanofilm to be tested, G j By the reduced modulus E j and Poisson's ratio j Equivalent calculation, j represents the subscript of different test systems; I1 is the contribution factor of the film to the membrane-substrate system, and a is the contact radius.

[0050] In some embodiments, the penetration load-depth curve has no obvious "advance" or "recession" phenomenon.

[0051] In some embodiments, the Poisson's ratio v j It is 0.1-0.5.

[0052] In some embodiments, the Poisson's ratio v j is 0.3.

[0053] The present invention also provides a system for acquiring mechanical characteristics of ultra-thin nano-film materials, the system comprising:

[0054] A loading unit, used for applying n different loads to the membrane-substrate system to be tested;

[0055] A detection unit, used to detect the penetration depth of the indenter and record the relationship between the penetration depth and the penetration load;

[0056] The reduced modulus calculation unit is used to calculate the reduced modulus of the membrane-substrate system under each indentation load through the Oliver-Pharr model according to the relationship between the depth and the indentation load;

[0057] A mechanical characteristic acquisition unit, configured to calculate the elastic modulus E of the nanometer thin film and the elastic modulus E of the substrate in the film-substrate system by fitting according to the reduced modulus E ri , the maximum indentation depth h i and the thickness t f , and the formula is formula (1): s In the formula: χ is a correction factor, which is determined by the contribution degree of the substrate effect under the critical indentation depth; i = 1, 2, 3,..., n.

[0058]

[0059] The acquisition system provided by the present invention is developed for studying the mechanical properties of ultra-thin nanometer thin films. A sharp Berkovich / Vickers indenter is used to perform indentation tests on the nanometer thin film at different penetration depths to achieve accurate evaluation of the mechanical properties of ultra-thin nanometer thin film materials. It can not only break through the limitation that ultra-thin films are difficult to meet the 10% critical indentation depth criterion, but also accurately test and characterize nanometer thin films with unknown substrate material properties.

[0060] The calculation model formula (1) of the thin film mechanical properties applicable to the penetration condition of the nanometer thin film according to the present invention is obtained by the following method:

[0061] As shown in

[0062] Referring to Figure 2 , a sharp geometrically self-similar indenter can be equivalent to a conical indenter with a characteristic half angle of α according to the principle of equivalent projection area. It is assumed that the interface bonding performance between the nanometer thin film 3 and the substrate material 5 is good during the indentation process, where a1 and a2 are the contact radii of the sharp indenter 1 with the substrate material 5 and the nanometer thin film 3 respectively, and h c is the contact depth.

[0063] Based on the Sneddon model, a normalized variable x is defined. When 0 < x < 1, the expression of the indentation morphology 7 after the penetration of the nanometer thin film is

[0064] z = f(x), x = ρ / a2 (3)

[0065] In the formula: for any position on the indentation morphology 7, ρ is the radial displacement from the loading axis 2; z is the height from the reference plane 4. Through Hankle transformation and integral processing of the indenter geometry function, the indentation load P i and the indentation depth h i can be expressed as:

[0066]

[0067] In the formula: σ zz(ρ,0) is the average stress in the z direction of the indentation contact area, that is, Figure 2 The conical indenter shows a completely penetrating nanofilm condition, and the indentation morphology 7 is expressed as:

[0068]

[0069] At this time, according to the quantitative relationship between the indentation load and the average stress in the z direction and the geometric relationship of the indentation section, the indentation load and indentation depth are as shown in formula (6):

[0070]

[0071] Where: E rs and E rf are the nominal elastic modulus of the substrate material 5 and the elastic modulus of the nanofilm 3 respectively; Δ is the weight of the mechanical properties of the nanofilm in the mechanical properties of the film-substrate system. At the same time, the thickness t of the nanofilm 3 can be expressed by formula (7):

[0072]

[0073] Then according to the contact stiffness S expression:

[0074]

[0075] By combining equations (6) to (8), we can derive the film mechanical properties calculation model (1) applicable to nano-film pressure penetration conditions.

[0076] In view of the influence of the substrate effect during the nanofilm pressing process, when h i →t, then E ri =χE f , combined with the Song-Pharr model shown in formula (2), the correction factor χ described in formula (1) is calculated;

[0077] Embodiment 1,

[0078] The film-substrate system to be tested in this embodiment is a commercial indium tin oxide (ITO) single-layer nanofilm sputtered by magnetron sputtering as an example. The substrate material is Corning glass, and the nominal sputtering thickness is known to be 180nm. The size of the tested sample is 10mm×10mm×0.7mm (length×width×height). The specific test steps are as follows:

[0079] Step 1: A single layer of ITO nanofilm material is prepared by magnetron sputtering deposition. To ensure that the surface of the tested sample meets the surface quality requirements of the nanoindentation test, that is, the nanoindentation depth is not less than 20 times the surface roughness Ra of the specimen, the surface roughness of the nanofilm is 1.0 nm as tested by atomic force microscopy;

[0080] Step 2: A series of indentation tests with different indentation loads were carried out on the ITO nanofilm using an indentation test instrument equipped with a Berkovich diamond indenter. The indentation process adopted a load-controlled loading mode. The maximum indentation loads were 10 mN, 20 mN, 30 mN and 50 mN, respectively. The loading and unloading time were both 30 s. To ensure the calculation accuracy and reliability of the test method, at least 5 sets of repeatability tests were repeated for each indentation load, such as Figure 3 Shown are typical indentation load-displacement curves under different indentation loads;

[0081] Step three, such as Figure 3 As shown in Figure 2, when the maximum indentation load is 10 mN, the maximum indentation depth (253.17 ± 1.52 nm) also exceeds the thickness of the nanofilm (t = 180 nm). Therefore, the classic Oliver-Pharr model can be used to extract the reduced modulus of the film-substrate system at different indentation depths, and the following is plotted: Figure 4 The relationship curve between the reduced modulus and the maximum penetration depth is shown;

[0082] Step 4: Use formula (1) to Figure 4 The test results of reduced modulus and maximum indentation depth in the ITO film indentation test are fitted, and the fitting formula (9) is as follows:

[0083]

[0084] Among them, the degree of fit R 2 The value is 0.9917, which further determines that the elastic moduli of the ITO nanofilm and the substrate material are 146 GPa and 70.93 GPa, respectively.

[0085] The nanofilm 3 tested in the present invention has no significant surface and interface damage such as microcracks, peeling, and debonding of the film-substrate interface 6 during the pressing process, that is, the pressing load-depth (Ph) curve has no obvious "sudden advance" or "sudden retreat" phenomenon.

[0086] From the above, it can be seen that the present invention can achieve accurate evaluation of the mechanical properties of ultra-thin nanofilm materials by only using a sharp indenter to carry out a series of indentation tests with different penetration depths on the nanofilm.

[0087] The acquisition method of the present invention has a simple operation process. It can not only break through the limitation that ultra-thin films are difficult to meet the 10% critical indentation depth criterion, but also can accurately test and characterize nanofilms with unknown substrate material properties, providing a new method for studying the mechanical properties of ultra-thin nanofilms.

[0088] The above description is only a general example of the present invention and is not intended to limit the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all implementation methods here. Any modifications, equivalent substitutions, improvements, etc. derived from this should be included in the protection scope of the present invention.

Claims

1. A method for obtaining mechanical characteristics of ultra-thin nanofilm materials, characterized in that: The steps include: Step 1, judging whether the nanofilm in the film-substrate system to be tested meets the nanoindentation test requirements; the thickness t of the nanofilm is known; Step 2: Carry out n times of different maximum indentation loads P on the membrane-substrate system to be tested that meets the test requirements i Indentation test, maximum indentation depth h i >thickness t, and obtain the indentation load-depth curve; Step 3: Extract different maximum indentation loads P according to the indentation load-depth curve through the Oliver-Pharr model. i The reduced modulus E of the membrane-substrate system ri ; Step 4: According to the reduced modulus E ri , Maximum penetration depth h i The elastic modulus E of the nanofilm in the film-substrate system to be tested is calculated by fitting the formula (1) and the thickness t. f and the elastic modulus E of the substrate s ; In formula (1), χ is a correction factor, which is determined by the contribution of the base effect at the critical penetration depth; i = 1, 2, 3, ..., n.

2. The method for obtaining mechanical characteristics of ultra-thin nano-film materials according to claim 1, characterized in that: The correction factor χ described in formula (1) is calculated as follows: When h i →t, then E ri =χE f , the correction factor χ is calculated according to formula (2); Where: G r is the reduced shear modulus of the membrane-substrate system, G s is the shear modulus of the substrate, G f is the shear modulus of the nanofilm to be tested, G j By the reduced modulus E j and Poisson's ratio j Equivalent calculation, j represents the subscript of different test systems; I1 is the contribution factor of the film to the membrane-substrate system, and a is the contact radius.

3. The method for obtaining mechanical characteristics of ultra-thin nano-film materials according to claim 1, characterized in that: The indentation load-depth curve has no obvious "advance" or "retreat" phenomenon.

4. The method for obtaining mechanical characteristics of ultra-thin nano-film materials according to claim 2, characterized in that: The Poisson's ratio υ j It is 0.1-0.

5.

5. The method for acquiring mechanical characteristics of ultra-thin nano-film materials according to claim 4, characterized in that: The Poisson's ratio υ j is 0.

3.

6. A system for acquiring mechanical characteristics of ultra-thin nano-film materials, characterized in that: The system includes: A loading unit, used for applying n different loads to the membrane-substrate system to be tested; A detection unit, used to detect the penetration depth of the indenter and record the relationship between the penetration depth and the penetration load; The reduced modulus calculation unit is used to calculate the reduced modulus of the membrane-substrate system under each indentation load through the Oliver-Pharr model according to the relationship between the depth and the indentation load; A mechanical characteristic acquisition unit is used to obtain the mechanical characteristic according to the reduced modulus E ri , Maximum penetration depth h i The elastic modulus E of the nanofilm in the film-substrate system is calculated by fitting the thickness t f and the elastic modulus E of the substrate s , the formula is formula (1): Where: χ is the correction factor, which is determined by the contribution of the base effect at the critical penetration depth; i = 1, 2, 3, ..., n.

7. The ultra-thin nano-film material mechanical characteristics acquisition system according to claim 6, characterized in that: The correction factor χ described in formula (1) is calculated as follows: When h i →t, then E ri =χE f , the correction factor χ is calculated according to formula (2); Where: G r is the reduced shear modulus of the membrane-substrate system, G s is the shear modulus of the substrate, G f is the shear modulus of the nanofilm to be tested, G j By the reduced modulus E j and Poisson's ratio j Equivalent calculation, j represents the subscript of different test systems; I1 is the contribution factor of the film to the membrane-substrate system, and a is the contact radius.

8. The ultra-thin nano-film material mechanical characteristics acquisition system according to claim 7, characterized in that: The Poisson's ratio υ j It is 0.1-0.

5.

9. The ultra-thin nano-film material mechanical characteristics acquisition system according to claim 8, characterized in that: The Poisson's ratio υ j is 0.

3.

10. The ultra-thin nano-film material mechanical characteristics acquisition system according to claim 6, characterized in that: The nano film part in the film-substrate system to be tested has no significant microcracks, peeling, film-substrate interface debonding surface and interface damage during the pressing process.

Citation Information

Patent Citations

  • Method of measuring mechanical characteristics of magnetron sputtering aluminum thin film

    CN104913993A

  • Calculation method for shallow nanoindentation elasticity modulus based on molecular dynamics simulation

    CN107506522A